Efficiency and Risk of Thromboembolism Prophylaxis in Surgery. Clinico-Expertmental Results in 1434 General Surgery Patients - Koppenhagen, K.; Häring, R.; Zühlke, H.-V.; Wiechmann, A.; Weing, H.G. (Thrombosis and Haemostasis, 1979)
Between 1975 and 1978, the frequency of both postoperative thromboses and pulmonary embolisms and of side effects (hemorrhages,hematomas) was examined in 1434 general surgery patients with varying prophylaxis by the radiofibrinogen test and pulmonary perfusion scintigraphy (double nuclide tests). Patients were selected at random and divided into 5 groups 150 patients without prophylaxis; low-dose heparin: 212 patients 3 x and 491 patients 2 x 5000 IU daily; combination prophylaxis of heparin and hemostasis-influencing dihydroergotamine=DHE (2 x daily):2500 IU heparin + 0.5 mg DHE were given to 351 patients, 5000 IU heparin + 0.5 mg DHE to 330 patients. The results of the prospective study show that the lowest thromboembolism rate occurs when heparin application is combined simultaneously with the hemostasis-influencing effect of DHE. The radiofibrinogen test indicated the most effective prophylaxis in petients receiving the combination of heparin and DHE (5000 IU heparin + 0.5 mg DHE, 2 x daily). The postoperative thrombosis rate decreased from 16.1% to 7.7% compared to the group treated only with heparin. The embolism-induced perfusion disorders amounted to 2.6% under the combination compared to 4.7% with 3 x 5000 IU heparin. Side effects of the prophylaxis are dependent on the amount of heparin both in the singledrug, low-dose treatment and the combination therapy. The combination of 2500 IU heparin + 0.5 mg DHE (2 x daily) yielded both the lowest rate of side effects and the thromboembolism prophylaxis of the standard law-dose heparin . The total result documents the efficiency of the combined thromboembolism prophylaxis with hepar in and DHE.